Regulating Photocatalytic CO2 Reduction Kinetics through Modification of Surface Coordination Sphere - Feng, Chengyang; Bo, Tingting; Maity, Partha; Zuo, Shouwei; Zhou, Wei; Huang, Kuo‐Wei; Mohammed, Omar F.; Zhang, Huabin (Advanced functional materials, 2024)
Solar‐driven reduction of CO2 to value‐added products represents a sustainable strategy for mitigating the greenhouse effect and addressing the related green‐energy crisis. Herein, it is demonstrated that modifying the surface coordination sphere can significantly enhance the reaction kinetics and overall efficiency of CO2 reduction. More specifically, the decoration of isolated Mn atoms over the multi‐edged TiO2 nano‐pompons (Mn/TONP) upshifts the d‐band center that allows favorable CO2 adsorption. Ultrafast spectroscopy demonstrates the greatly accelerated charge transfer between photoexcited multi‐edged TONP and the newly implanted Mn reactive centers, supplying long‐lifetime electrons to reduce absorbed CO2 molecules. By integrating adsorption and activation functions into the newly decorated Mn sites, the developed photocatalyst demonstrate impressive capacity for CO2 reduction (80.51 mmol g−1 h−1). The surface modulation strategy at the atomic level not only opens new avenues for regulating the reaction kinetics toward photocatalytic CO2 reduction, but also paves the way for the rational design of highly efficient and selective photocatalysts for clean energy conversion. This study develops an efficient CO2 reduction photocatalyst by modifying isolated Mn sites on the TiO2 surface. The Mn site is proven to be a unified site for the adsorption and activation of CO2 molecules both experimentally and theoretically. Furthermore, this work explicitly reveals the influence of Mn species on the energy transfer process in photocatalytic CO2 reduction.